2017
DOI: 10.1007/s13197-017-2557-0
|View full text |Cite
|
Sign up to set email alerts
|

Particularities of Syrah wines from different growing regions of Southern Brazil: grapevine phenology and bioactive compounds

Abstract: The aim of this study was to monitor the phenological parameters of grapevine () of Syrah variety recently introduced in the region of Marari, Água Doce, Campos Novos and São Joaquim, Santa Catarina State (SC), Brazil, and to characterize the phenolic composition and antioxidant activity of wines produced from this variety of the vintages 2010 and 2011. The adaptation of the grapevine to climate conditions of these grape growing regions of Southern Brazil for this variety has also been assessed. The climate va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
1
13
1
Order By: Relevance
“…The tyrosol was detected at high concentrations in all samples of sparkling wines analyzed (Table and ). The concentration of tyrosol in the rosé sparkling wines in this study is higher than values previously reported for sparkling wines (Pozo‐Bayón, Hernández, Martín‐Álvarez, & Polo, ; Stefenon et al., ) and red wines (Gris et al., ; Sartor et al., ). It was observed that the addition of enological agents influenced the tyrosol concentration of the wines at the end of aging (T12) in relation to the control sample (Table and ).…”
Section: Resultscontrasting
confidence: 73%
“…The tyrosol was detected at high concentrations in all samples of sparkling wines analyzed (Table and ). The concentration of tyrosol in the rosé sparkling wines in this study is higher than values previously reported for sparkling wines (Pozo‐Bayón, Hernández, Martín‐Álvarez, & Polo, ; Stefenon et al., ) and red wines (Gris et al., ; Sartor et al., ). It was observed that the addition of enological agents influenced the tyrosol concentration of the wines at the end of aging (T12) in relation to the control sample (Table and ).…”
Section: Resultscontrasting
confidence: 73%
“…Phenolic compounds such as flavonols and flavanols, mainly quercetin and catechin, as well as anthocyanins are generally associated with the antioxidant properties of red wines. [1,4,8] Indeed, the antioxidant activity was positively correlated with the phenolic content of all varietal wines (data not shown). All wines had abundant concentrations of monomeric and polymeric anthocyanins, and of both polymerised and non-polymerised polyphenols, determined as equivalents of catechin.…”
Section: Resultsmentioning
confidence: 88%
“…In fact, during the vintage period of 2011, the rainfall was approximately 1100 mm in the region of Campos Novos, while during the vintage of 2012, the rainfall was lower, approximately 900 mm. [8] The Ancellotta wines showed the highest colour intensity and colour density, with values up to 44.08 and 38.89, respectively, in wine samples from the vintage 2012. In comparison to the other wine varieties, the colour indexes were greatly lower in Nebbiolo wines.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations